Laju Pertumbuhan Ikan Nila (Oreochromis niloticus) pada Tiga Sistem Resirkulasi yang Berbeda - Yessica Christin; I Wayan Restu; Gde Raka Angga Kartika (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2021)
Recirculation aquaculture system can be used to maintain the water quality during fish maintenance. This research aimed to determine the growth rate and survival rate of Tilapia (Oreochromis niloticus) by used three different recirculation system. The treatments are recirculation without filter (control), a biofilter system (bioball) and aquaponic systems (using water spinach and caisim). During eight weeks, the resulted of research showed the highest growth rate of Tilapia (Oreochromis niloticus) in biofilter treatment amounted for 4.58%/day followed by the control treatment for 4.09%/day and the lowest in aquaponic treatment for 3,81%/day. The best survival rate of Tilapia (Oreochromis niloticus) during the research contained in aquaponic treatment followed by biofilter treatment and the lowest value was in control treatment. During the research, of aquaponic treatment gave survival rate for 78.7%, biofilters 74.8% and control treatment for 63.5%. There were no significant differences (P > 0,05), between parameters for growth while survivl rate was significant (P < 0.05). The parameters of water quality include temperature, potential hidrogen (pH), dissolved oxygen (DO) and total dissolved solids (TDS). The quality range of water in all treatments generally described that the range were still running in tolerance for growth and survival rate of Tilapia.